U2504 Determines the Species Specificity of the A-site Cleft Antibiotics. The Structures of Tiamulin, Homoharringtonine and Bruceantin Bound to the Ribosome - Gürel, Güliz (2009)
Structures have been obtained for the complexes tiamulin, homoharringtonine and bruceatin form with the large ribosomal subunit of Haloarcula marismortui at resolutions ranging from 2.8 to 3.2 Å. They show that these inhibitors all block protein synthesis by competing with the amino acid side chains of incoming aminoacyl-tRNAs for binding in the A-site cleft in the peptidyl transferase center, which is universally conserved. In addition these structures support the hypothesis that the species-specificity exhibited by the A-site cleft inhibitors is determined by the interactions they make, or fail to make, with a single nucleotide, U2504 (E. coli). In the ribosome, the position of U2504 is controlled by its interactions with neighboring nucleotides, whose identities vary among kingdoms.